Barriers and Facilitators to Diabetes Self-Management in Pregnant Women with Pre-existing Type 2 Diabetes Mellitus: A Scoping Review - Phonyiam R. (2023)
Background: Pregnant women with pre-existing type 2 diabetes mellitus (T2DM) are at risk of poor maternal and neonatal health outcomes. Previous systematic reviews on pregnant women with T2DM have focused on physical activity, blood glucose monitoring, and insulin injections. Objective: The purpose of this scoping review was to examine the barriers and facilitators to diabetes self-management in pregnant women with pre-existing type 2 diabetes mellitus. Methods: PubMed, CINAHL, and EMBASE databases were searched using the PRISMA-ScR guidelines. Inclusion criteria included manuscripts written in English and qualitative studies. Con-sensus statements were excluded. A metasummary was used to identify patterns in barriers and fa-cilitators across studies. A vote-counting method was used to summarize qualitative findings. Results: A total of ten qualitative publications were selected. This review suggests four themes de-scribing barriers, including barriers to diabetes self-management in pregnancy, stress related to pregnancy with diabetes, a barrier to access to health care, and sensing a loss of control. The fifth theme described facilitators of diabetes self-management in pregnancy. Conclusion: This supports an integrative model of maternity care and culturally relevant practices to overcome critical barriers and optimize key facilitators to enhance diabetes self-management behaviors and improve maternal and neonatal health outcomes.